The pacification of the Favelas: mega events, global competitiveness, and the neutralization of marginality - Saborío, Sebastián (2013)
Rio de Janeiro is preparing to host two major sporting events in the coming years: the 2014 FIFA World Football Cup and the 2016 Olympic Games. Local authorities are promoting these mega events as an opportunity to increase the global competitiveness of the city. But in order to attract private capital from the global economy it is not enough for Rio to showcase the city as capable of organizing and implementing these events. Rather, the authorities must also demonstrate that what has been considered one of the most dangerous cities in the world can now become a safe place for business. To do so, what has been promoted as a new model of ‘community policing’ the UPP (Pacifying Police Units) has been implemented since 2008 in 107 favelas. The majority of the favelas involved in the program are situated around the sites where these mega events will take place and around other wealthy areas of the city. This article analyses the relation between mega events, global competitiveness and the neutralization of local marginality